128k views
4 votes
I keep messing up I cant get the answer help

I keep messing up I cant get the answer help-example-1

2 Answers

4 votes

So, let’s first simplify each side:

For the left side:

-3 * (x + 2) = -3x - 6

For the right side:

6 + 2x + 8 = 2x + 14

So, since they equal each other:

-3x - 6 = 2x + 14

Now add 3x to both sides:

-6 = 5x + 14

Subtract 14 from both sides:

5x = -20

Divide by 5:

x = -4

And, there’s your answer!

User Whp
by
4.8k points
5 votes

-3(x+2)=6+2x+8

first we distribute -3 over the bracket

-3x-6=6+2x+8

combining like terms

-3x-6=2x+14

bring 2x on the left

-3x-2x-6=14

-5x-6=14

bring -6 to the right side

-5x=14+6

x=20/-5=-4

User Aditya Gupta
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.